2022
DOI: 10.1155/2022/6565109
|View full text |Cite|
|
Sign up to set email alerts
|

Early Assessment of Cardiac Function by Echocardiography in Patients with Gestational Diabetes Mellitus

Abstract: Objective. To offer a baseline for clinical diagnosis, echocardiography was performed to evaluate the disparities in heart function comparing pregnant women with diabetes mellitus (GDM) and ordinary pregnant women. Methods. A prospective case-control study is being conducted on pregnant women with or without gestational diabetes. The sample size for both the intervention and control groups is the same: no diabetes diagnosis or previous forms, a single pregnancy, and no issues (such as preeclampsia or fetal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%